Analisis Komparatif Teori Perdagangan Internasional Modern dalam Perspektif Ekonomi Konvensional dan Islam - Restia Restia; Ahmad Daffa Dhiyailhaq; Muhammad Zulqurnain; Mohammad Fikal Adhitiya; Nur Kholis Ridwan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This research aims to compare modern international trade theories from conventional and Islamic economic perspectives. The technique used is a literature review through the analysis of sources from journals, books, and related research. The findings of this research indicate that international trade theory in the conventional perspective prioritizes efficiency, specialization, and increased profits through free market mechanisms, such as the theory of absolute advantage, comparative advantage, the H-O factor proportion, and the theory of large-scale economies. However, this approach often overlooks moral aspects, distributional justice, and the risk of exploitation. On the other hand, the Islamic perspective views trade as a muamalah activity based on justice, trustworthiness (amanah), the prohibition of riba (interest), gharar (uncertainty), and maisir (gambling), as well as the objectives of maqasid sharia (the objectives of Sharia). Both views recognize the importance of trade for economic growth but differ in their basic values and ethics. In today's era of globalization and digitalization, the importance of integrating Islamic values into international trade is increasingly understood. This aims to build a more just, sustainable, and inclusive trading system. This research emphasizes the need to apply Sharia principles in contemporary trade practices, including the application of Islamic financial instruments, the development of halal e-commerce platforms, and ethical oversight within global supply chains. In this way, it is hoped that international trade can provide broader benefits to all of humanity, in accordance with the principles of justice and welfare in Islam. The interconnectedness of both approaches in the digital context demonstrates the need to unite Islamic moral values with changes in today's global trade.